2017
DOI: 10.1111/asj.12882
|View full text |Cite
|
Sign up to set email alerts
|

Dietary methionine source and level affect hepatic sulfur amino acid metabolism of broiler breeder hens

Abstract: A study was carried out to investigate the effects of dietary methionine source and level on plasma free amino acids patterns and the expression of genes involved in hepatic methionine metabolism in broiler breeders. A total of 2184 broiler breeders were assigned to 13 dietary treatments, with eight replicates per treatment. The 13 treatments included one control group and 12 additional treatments employing two sources and six levels (0.05, 0.10, 0.15, 0.20, 0.25 and 1.00%). Higher plasma methionine concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
3
9
0
1
Order By: Relevance
“…When the Met was supplied insufficiently, the levels of Ser and Cys may be altered ( 36 ). At week 16, the lower content of Ala in Met- group was observed, which was consistent with the study by Wan et al ( 37 ). They found that plasma Ala concentration was linearly increased as DL-Met supplementation level increased.…”
Section: Discussionsupporting
confidence: 92%
“…When the Met was supplied insufficiently, the levels of Ser and Cys may be altered ( 36 ). At week 16, the lower content of Ala in Met- group was observed, which was consistent with the study by Wan et al ( 37 ). They found that plasma Ala concentration was linearly increased as DL-Met supplementation level increased.…”
Section: Discussionsupporting
confidence: 92%
“…As one of MAT isomerases, mat2a is essential to modulate catalytic activity of MAT. In the current study, compared to the higher mat2a level in shrimp fed the PC diet, methionine deficiency signals in the NC group caused the reduction of methionine consumption in methylation cycle ( Wan et al, 2017 ). Most marine animals cannot synthesize enough taurine by themselves to fulfil the requirement for healthy growth and development ( Tong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 65%
“…The endogenous AAs were referred to those coming from cellular proteolysis and de novo AA synthesis inside of the body, while the exogenous AAs were referred to those obtained from the dietary supply outside of the body. In laying hens, the increasing methionine supplementation induced a linear increase in plasma concentrations of Ala, Tyr, Val, Gly, and Ser ( Wan, et al., 2017 ), and serum albumin level increased significantly in response to supplemental L-Val ( Azzam, et al., 2015 ). The disappearance of AAs from blood pool was mainly influenced by the absorption from blood by cells for synthesis of new proteins or by utilization as fuel for body energy requirement ( Liao, et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%